2021
DOI: 10.1111/cobi.13801
|View full text |Cite
|
Sign up to set email alerts
|

Wild meat trade over the last 45 years in the Peruvian Amazon

Abstract: The trade in wild meat is an important economic component of rural people's livelihoods, but it has been perceived to be among the main causes of the decline of wildlife species. Recently, the COVID-19 pandemic has brought to light an additional concern of wildlife markets as a major human-health challenge. We analyzed data from the largest longitudinal monitoring of the most important urban wild-meat markets in Iquitos, Peru, to examine the trends in and impacts of these markets on people's livelihoods. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In contrast, in flooded forests the WLPs showed less-extreme oscillations of 7.7 ind./km 2 +- 3.4 (SD), but also disappeared between 2013 and 2017 following historically high and prolonged floods that began in 2011 and lasted through 2015. This regional disappearance following extreme flooding was reflected in meat sales in the Iquitos bush meat market, which provides a measure of WLP harvest from the Loreto Region, an area of 38-million ha that includes the Yavari landscape [ 45 ]. In 1996 there were 4,510 individuals sold, in 2006 3,170 were sold, and then a dramatic decrease was seen in 2013 when only 253 WLP were sold.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in flooded forests the WLPs showed less-extreme oscillations of 7.7 ind./km 2 +- 3.4 (SD), but also disappeared between 2013 and 2017 following historically high and prolonged floods that began in 2011 and lasted through 2015. This regional disappearance following extreme flooding was reflected in meat sales in the Iquitos bush meat market, which provides a measure of WLP harvest from the Loreto Region, an area of 38-million ha that includes the Yavari landscape [ 45 ]. In 1996 there were 4,510 individuals sold, in 2006 3,170 were sold, and then a dramatic decrease was seen in 2013 when only 253 WLP were sold.…”
Section: Resultsmentioning
confidence: 99%
“…Habitat destruction and drought causes reduced food availability and large mammals become concentrated in smaller forest blocks, or around small ponds with greater resource competition, and where hunters have greater success [42]. In the tierra firme forests of western Amazonia studies have shown hunting is generally sustainable and does not cause population declines of WLP with no known cumulative impacts (18,(43)(44)(45). In regions that have cumulative impacts (flooded forests, Meso-America, Southern SA) the WLP populations have more severe disappearances and slower recoveries.…”
Section: Plos Onementioning
confidence: 99%
“…In the Central Brazilian Amazon, rural migrants continue to consume wild meat after moving to urban areas (Chaves et al, 2021). In Iquitos, in the Peruvian Amazon, the increase in wild meat sales has kept pace with urban population growth from 1973 to 2018 (Mayor et al, 2022). Thus, urban demand may affect the stock of game species that can be accessed by the rural population, which is dependent on this resource (Morsello et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Home range and habitat vary across individual species. Paca, collared peccary, white-lipped peccary, and brocket deer consist of nearly 90% of the total biomass sold in the markets of Iquitos in 1973–2018 ( 55 ). Lowland tapir, white-lipped peccary, woolly monkey, and spider monkey have been classified as vulnerable species according to International Union for Conservation of Nature and Natural Resources (IUCN).…”
Section: Methodsmentioning
confidence: 99%